PENGARUH PENGALAMAN USAHA DAN PENGGUNAAN INFORMASI AKUNTANSI PELAKU USAHA MIKRO KECIL MENENGAH TERHADAP KEBERHASILAN USAHA - Khoirunnisa Cahya Firdarini (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2019)
Accounting information has an important role to achieve business success, as well as for small businesses.This research examines the effect of business experience and accounting information system used toward business success with age of business as control variable. The population of this research are small and medium enterprises (SMEs) in creative industries sector operated in Yogyakarta district. Based on purposive sampling method, total sample of this research is 200 SMEs. Statistical tool utilized to test the hypothesis in this study is path analysis using structural equation modelling (SEM). The test result shows that business experience and accounting information have positive and significant effect to the success of SMEs.